Isolation of hemicellulose from rice straw by alkaline extraction / Athirah Zawani Amran - Amran, Athirah Zawani (2010)
An alkaline extraction method was developed for the extraction of two types of hemicellulose; hemicellulose with lignin (HL) and hemicellulose without lignin (HWL) from rice straw. The extraction of hemicellulose was done using sodium hydroxide (NaOH). Hemicellulose is an alkaline soluble compound; therefore extraction using NaOH is the most suitable method to isolate hemicellulose especially from non-woody plants such as rice straw. Several factors such as NaOH concentration, temperature and pH were optimized for maximum production of these hemicelluloses. Rice straw was mixed with NaOH at concentration of 1 % - 5 %, temperature of 45 °C - 65 °C and at pH of 4.5 - 6.5. The determination of hemicellulose concentrations were done using UV - Visible Spectrophotometer and the hemicellulose concentrations were analyzed by determining the total sugar. The results showed that the optimum condition for the extraction of HL was at 1 % of NaOH, 65 °C and pH of 5.5 while for the extraction of HWL, the optimum conditions was at 3 % NaOH, 45 °C and pH of 5.5. The concentration for HL determined using UV - Visible Spectrophotometer at 1 % NaOH, temperature of 65 °C and pH 5.5 were 7.44 ug/mL, 18.01 ug/mL and 22.99 ug/mL, respectively. On the other hand, the HWL concentration at optimum NaOH concentration, temperature and pH were 32.06 ug/mL, 63.56 ug/mL and 33.77 ug/mL, respectively.